The Ethics Of Utilitarianism And Its Relevance To Islamic Religious Education - Eva Rojiatul Afwa (ATTAQWA: Jurnal Pendidikan Islam dan Anak Usia Dini, 2023)
In Islam itself, the word ethics is equivalent to the word "morals". In simple terms, akhlak or khuluq in Arabic is translated as character, manners, and similar translations. For this reason, khuluq or morals are movements of the soul that are more about actions or behavior. So that ethics or morals become something very important to study and implement in people's daily lives. Utilitarianism is part of a discussion of moral philosophy, especially teleology. The actions that humans do must be good actions and not despicable actions. So as to bring benefits and happiness to as many people as possible. Through John Struat Mill's concept of utilitarianism which has relevance to Islamic sciences or thought, it is not impossible that Islam, as a universal religion, can be felt for its goodness by Muslims and also by all mankind, including non-Muslims. The challenge faced in the world of education, especially Islamic Religious Education as a field of study is how to implement Islamic religious education not only to teach knowledge about religion, but also how to direct students to have the qualities of faith, piety and noble character . At present the urgent issue is what efforts must be made by educators to develop approaches in Islamic education so that they can broaden students' understanding and encourage them to practice it and at the same time shape their character and personality.